The Rise of Conservative Islam in the Indonesian Political Constellation - ., Abdul Rahman; ., Nurlela; ., Jumadi (KnE Social Sciences, 2024)
Pancasila as the basis of the state has an important position in the social order of the nation and state. Pancasila, which was extracted from the values and local wisdom of the archipelago, was agreed upon by the founders of the nation as a sentence that binds various ethnic groups, religions, races, and between groups who claim to be Indonesian citizens. However, with the development of science and the emergence of a war of thought, Pancasila is currently starting to receive a serious challenge from conservative Islamic groups who doubt and even reject the existence of Pancasila as the state ideology. They consider that Pancasila has failed to become an inspiration for the government in realizing the welfare of the people, so that as a country with a Muslim majority, Indonesia should implement Islamic law. In the midst of the shock of conservative Islam, there is also an attitude of hypernationalism that both claim to be Pancasila People. In the name of Pancasila, they reject the involvement of foreign companies, capital, and workers in managing state assets. On the other hand, in the name of maintaining Pancasila as the state ideology, there are often actions taken by the government that are considered severe against conservative Islamic groups which further is assumed to endanger the sovereignty of the state. Keywords: Pancasila, conservative Islam, hypernationalism